Metastable Liquid-Liquid Phase Separation and Aging Lead to Strong Processing Path Dependence in Mini-Spidroin Solutions - Fedorov, Dmitrii; Sammalisto, Fred-Eric; Harmat, Adam L.; Ahlberg, Martin; Koskela, Salla; Haataja, Mikko P.; Scacchi, Alberto; Sammalkorpi, Maria; Linder, Markus B. (WILEY-V C H VERLAG GMBH, 2025)
Recombinant silk proteins provide a route toward sustainable and biocompatible materials. For making such materials, the assembly process from dilute protein into a functional material is central. The assembly mechanism in engineered materials is by necessity different from the natural ones-this poses challenges but also opens opportunities for scaling up and for developing novel properties. The phase behavior of a mini-spidroin, NT-2Rep-CT is studied, which is a widely studied variant of recombinant silk. NT-2Rep-CT can be triggered to assemble by lowering the pH, but even at high pH-considered as storage conditions-it can be in various states, such as forming condensates, clusters, gels, and soluble protein. It is shown how its assembly phases evolve through both metastable and dynamically arrested states. The observed behavior of silk protein solutions is highly complex, and elements thereof from phase diagrams associated with polymers, colloidal systems, and globular proteins are found. Based on the characterization of cluster formation and structural intermediates, a minimalist phase diagram is proposed for NT-2Rep-CT and argues that the understanding and insight into silk assembly via its phase behavior, and especially the arrested states, is central for designing recombinant silk proteins and their processing for materials applications.